Sanhuang Xiexin Tang Ameliorates Type 2 Diabetic Rats via Modulation of the Metabolic Profiles and NF-κB/PI-3K/Akt Signaling Pathways - Wei, Xiaoyan; Tao, Jinhua; Shen, Yumeng; Xiao, Suwei; Jiang, Shu; Shang, Erxin; Zhu, Zhenhua; Qian, Dawei; Duan, Jinao (Frontiers in Pharmacology, 2018)
Sanhuang Xiexin Tang (SXT), a classic prescription, has been clinically used to cure diabetes for thousands of years, but its mechanism remains unclear. Here, a systematic in-depth research was performed to unravel how it worked by the signaling pathway and metabonomics analysis. Our studies were conducted using high-fat diets (HFD) and streptozocin (STZ)-induced type 2 diabetes mellitus (T2DM) rats. The blood glucose was measured by a glucose-meter. Protein contents were determined by western blotting or ELISA and mRNA expression was identified by RT-PCR analysis. The pathological status of pancreas was assessed by histopathological analysis. Furthermore, Ultra Performance Liquid Chromatography-Quadrupole-Time of Flight/Mass Spectrometry (UPLC-Q-TOF/MS) coupled with multivariate statistical analysis was performed to discover potential biomarkers and the associated pathways. Hyperglycaemia, insulin resistance, dyslipidemia and inflammation in T2DM rats were significantly ameliorated after seven-week oral administration of SXT. The expressions of phosphatidylinositol-3-kinase (PI-3K), protein kinase B (Akt), glucose transporters-4 (GLUT4) mRNA and p-PI-3K, p-Akt, GLUT4 protein involved in the PI-3K/Akt signaling pathway of T2DM were markedly up-regulated. Further investigation indicated that the perturbance of metabolic profiling in T2DM rats was obviously reversed by SXT and 38 potential biomarkers were screened and identified. Our study might help clarify the mechanism of SXT and provide some evidences for its clinical application in the future.